Motivação para o aprendizado da música: um estudo de caso com músicos de orquestra - Marcelo de Magalhães Cunha (2013)
Motivation refers to the balance of affective and emotional structures that provide the regulation of mental or cognitive schemes. Motivation for the study and learning of erudite music, also known as classical music, is one of the great challenges posed to students of this area, due to the daily efforts and concentration required by the activities, both the physical motor ones involved in learning a musical instrument, and those involving the understanding of the language, writing and memory development. The main goal of this research is to investigate how professional orchestra musicians have found motivation for the study and learning of classical music in their relationships with people from their families and music schools. The revised publications regarding musical education approach motivation indirectly, analyzing it more from the relationship with the musical object, and whenever dealing with interrelationships are more focused on those established with school people. This research will concentrate to understand on how the emotional and affective aspects, resulting from the interrelationships with family as well as school peoples, contribute to the construction of motivation for classic music learning. As theoretical referentials, I have used the question of moral principles, that helping the equilibration of affective schemes, as in Piagets theory, and the way mediation through others may favor the construction of sense, from Vygotskys point of view. The attempt was to understand how some orchestra musicians found motivation for the study of musical language and instruments from the interrelationships with parents, siblings, schoolmates and teachers. Case studies of six professional musicians of one of Brazils symphonic orchestras who stated through individual and group interviews how their relationships with family and school people, at the time they were music students, awakened or not their motivation, and how their interest in music learning was built. As some of the interviewed musicians were of different nationalities, it was possible to observe motivation in diverse cultural and educational environments as well. The conclusion was that all of them ended up building their own regulatory schemes from the interrelations experienced. We observed that some found motivation through family and/or school more than others, based on self-regulation and from the equilibration of affective schemes and the sense that older people, parents, siblings, schoolmates or teachers represented from the moral point of view to the interviewed musicians. In the musical education context, teachers play an important role not only as content transmitters, but also as co-builders of affective and cognitive regulations, due to the fact that they symbolize family people, a fact that helped in the motivational process experienced by the interviewed musicians.